To see the invisible : Karelian rock art - Faradzhev, Arsen, (Archaeopress open access., 2015)
This contribution considers 25 years of discovery of the possible origins and development of the Rock Art Tradition to create Karelian Rock Art images under the open sky through the analysis of different types of intercessions into the horizontal surface of granite rocks.